Research on Interactive Teaching Strategies in Smart Classrooms Under the Background of Digital Technology—Focused on the Theoretical Courses of Digital Media Art Majors (Journal of Global Arts Studies, 2025)
Background: The deep integration of digital technology and education has provided strong technical support for the development of smart education. How to improve interactive teaching strategies in smart classrooms in order to enhance teaching effectiveness has become an urgent issue to be addressed. Objective: This study aims to propose improved strategies for interactive teaching in smart classrooms through systematic research and practical exploration. Methods: Through literature review, the concepts of smart classrooms and interactive teaching elements were clarified. An interactive teaching strategy for the course Introduction to Art was designed and implemented, followed by questionnaire surveys and analytical evaluation, based on which improvement strategies were proposed. Results: The findings indicate that smart classroom interactive teaching strategies have significant effects in enhancing students’ learning interest, classroom participation, and professional skills. Interactive teaching in smart classrooms can better satisfy students’ learning needs and promote the continuous improvement of educational informatization and teaching quality. Conclusion: By optimizing smart classroom infrastructure, strengthening the application of interactive technologies, enriching digital resources, and improving teacher–student interaction, the effectiveness of interactive teaching can be significantly enhanced. In the future, smart classroom interactive teaching will further develop toward intelligent technologies, precise resource allocation, and personalized teaching, thereby providing a high-quality educational environment and learning experience for cultivating high-level digital media art talents.
Keywords: Digital Technology; Smart Classroom; Interactive Teaching; Digital Media Art